Pneumonias em Bovinos Neonatos - Rocha, Marcelo Nogueira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Pneumonia is a respiratory disease that most affects the cattle, especially calves, which according to their anatomical and physiological characteristics are more susceptible to respiratory diseases compared to other large mammals. Therefore, prevention of pneumonia is a key factor to minimize the possible economic losses generated by the early involvement of a calf by these diseases, which can cause a decrease in animal development. Despite the multifactorial etiology and classification on the types of pneumonia is still subject of discussion, most pneumonias are in three categories: bronchopneumonia, interstitial pneumonia and metastatic pneumonia, the first being the most important among them. Clinical signs vary with the cause, but are classified as medical conditions ranging since subclinical to clinically irreversible. Treatment depends on the clinical experience and can associate drugs for alleviating the symptoms with anti-inflammatories and antibiotics. Thus, premature diagnosis is directly linked to prognosis, treatment costs and spread of the disease

A pneumonia é a doença respiratória que mais afeta os bovinos, principalmente os bezerros, que em função de suas características anatomofisiológicas são mais susceptíveis às doenças do trato respiratório em relação aos outros mamíferos de grande porte. Sendo assim, a prevenção da pneumonia é um fator chave para minimizar as possíveis perdas econômicas geradas pelo acometimento precoce de um bezerro por essas doenças, que podem causar um déficit no desenvolvimento do animal. Apesar da etiologia multifatorial e a classificação quanto aos tipos de pneumonia ainda ser tema de discussão, a maioria das pneumonias encontram-se em três categorias: broncopneumonia, pneumonia intersticial e pneumonia metastática, sendo a primeira a mais importante entre elas. Os sinais clínicos variam de acordo com a causa, mas são classificados em estados clínicos que variam de subclínico á clínico irreversível. O tratamento depende da experiência do clinico e pode associar medicamentos que amenizem os sintomas, com antiinflamatórios e antibióticos. Assim, o diagnóstico precoce está diretamente ligado ao prognóstico, custo do tratamento e disseminação da doença
Keywords: Bovino - Doenças; Pneumonia; Neonatologia veterinária; Respiratory Disease; Pneumonia; Clinical Signs